واقع المراجعة الحكومية في سورية وإمكانية اعتماد معايير المراجعة الحكومية GAO كمعايير محلية "دراسة ميدانية على فروع الجهاز المركزي للرقابة المالية في سورية" - العربيد عصام فهد; العثمان محمد نادر; عاصي أحمد عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول هذا البحث تقويم واقع عمل مفتشي الجهاز المركزي للرقابة المالية في سورية ودراسة إمكانية تبني معايير المراجعة الحكومية GAO الصادرة عن مكتب المحاسبة العام, كمعايير مراجعة حكومية في سورية, من وجهة نظر المفتشين العاملين في الجهاز المركزي للرقابة المالية, وفي سبيل ذلك تناول البحث عرضاً لأهم معايير المراجعة الحكومية سيما المعايير الصادرة عن GAO, كما تناول الأجهزة الرقابية الحكومية السورية, ومراحل تطورها وآلية عمل مفتشي الجهاز المركزي للرقابة المالية, ومن ثم تقويم عمل هذه الأجهزة بناءً على إجراء مقابلات شخصية وميدانية مع المفتشين أثناء قيامهم بأداء عملهم, وبالتالي الوقوف عند أهم المعوقات والصعوبات التي يعانون منها, وفي سبيل التحقق من إمكانية تطبيق هذه المعايير فقد صممت قائمة استبانة تتضمن مجموعة من العبارات ومجموعة من المقترحات لسير عملية المراجعة في الجهاز من واقع معايير المراجعة الحكومية GAO, ليتم من خلالها استطلاع رأي عينة البحث والتي تمثلت بـ 140 مفتشاً يعملون في ثلاث محافظات سورية. وقد بينت الدراسة رغبة أفراد العينة بتغيير واقع المراجعة الحكومية الحالي, من عدة نواحٍ سواء من حيث التأهيل العلمي والعملي أومن حيث الاستقلال عن السلطة التنفيذية بالإضافة إلى الرغبة بالقيام بعملية المراجعة بشكل منظم ومخطط له سابقاً وهذا بدوره يوفر الأرضية المناسبة لتبنّي معايير مراجعة حكومية. This research assessment of the reality of the work of inspectors of the Central Agency for Financial Control in Syria and study the possibility of adopting auditing standards governmental GAO issued by the General Accounting Office, criteria government review in Syria, from the standpoint of the inspectors working in the Central Agency for Financial Control, in order that touched on a presentation of the most important auditing standards governmental particular standards issued by the GAO, also addressed the regulatory bodies Syrian government, and the stages of development and the mechanism of action of inspectors of the Central Agency for Financial Control, and then assess the work of these devices based on interviews and field with the inspectors while they perform their work, and therefore stand at the most important obstacles and the difficulties which they suffer, in order to verify the possibility of the application of these standards has been designed list of identification include a set of phrases and a set of proposals for the conduct of the review process in the device from the reality of auditing standards governmental GAO, to be through an opinion poll research sample, which were represented by 140 inspectors working in the three provinces Syria. The study showed the desire of the sample to change the reality of auditing government now, in many ways, both in terms of rehabilitation scientific and practical believe in terms of independence from the executive branch as well as the desire to carry out the audit in an orderly and planned previously and this in turn provides a suitable ground for the adoption of governmental auditing standards.